Ultrastructural analysis of the fat body in workers of Attini ants (Hymenoptera: Formicidae) - Roma, Gislaine C. [UNESP]; Bueno, Odair C. [UNESP]; Camargo-Mathias, Maria I. [UNESP] (Brill Academic Publishers, 2009)
In the present study a comparative morphological analysis of the fat body cells of ant workers of the basal Attini species Cyphomyrmex rimosus and Mycetarotesparallelus, and the derived species Acromynnex disciger and Atta laevigata was conducted. The results revealed that the fat body is located mainly in the abdomen around organs (perivisceral) and near the integument (parietal). The main cells observed are spherical or polygonal trophocytes with a slightly rough surface. The oenocytes, another cell type found, are closely associated with trophocytes, and present a spherical or polygonal shape and a smoother surface. The morphometric analysis showed that the area of trophocytes and oenocytes of C rimosus and M parallelus is significantly smaller when compared to those of A. disciger and A. laevigata. In the cytoplasm of parietal and perivisceral trophocytes and oenocytes, electronlucent droplets (probably lipids) and electrondense granules (probably proteins) indicate the participation of these cells in the storage of these elements, while digestive vacuoles, residual bodies, and multivesicular bodies suggest a role in intracellular digestion. In perivisceral trophocytes and oenocytes of C rimosus, the presence of mitochondria, lamellar rough endoplasmic reticulum, and Golgi complex suggests that these cells synthesize proteins. Based on these data, no significant differences were observed between the fat body cells of basal and derived ants, except regarding the larger size of trophocytes and oenocytes of the derived species A. disciger and A. laevigata. (C) Koninklijke Brill NV, Leiden, 2009
Keywords: Trophocyte; oenocyte; morphology; morphometry; ultrastructure